UV Spectrophotometric Method for theEstimation of Itopride Hydrochloride in Pharmaceutical Formulation - K. R. Gupta; R. R. Joshi; R. B. Chawla; S. G. Wadodkar (E-Journal of Chemistry)
Three simple, precise and economical UV methods have been developed for the estimation of itopride hydrochloride in pharmaceutical formulations. Itopride hydrochloride in distilled water shows the maximum absorbance at 258.0 nm (Method A) and in first order derivative spectra of the same shows sharp peak at 247.0 nm, when n = 1 (Method B). Method C utilises area under curve (AUC) in the wavelength range from 262.0-254.0 nm for analysis of itopride hydrochloride. The drug was found to obey Beer-Lambert’s law in the concentration range of 5-50 μg/mL for all three proposed methods. Results of the analysis were validated statistically and recovery studies were found to be satisfactory.